2000
DOI: 10.1161/01.hyp.35.2.e1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Telemetric Recording of Arterial Pressure and Heart Rate in Mice Fed Basal and High NaCl Diets

Abstract: Abstract-Research examining the control of arterial pressure in mice has primarily relied on tail-cuff plethysmography and, more recently, on tethered arterial catheters. In contrast, the radiotelemetry method has largely become the "gold standard" for long-term monitoring of arterial pressure and heart rate in rats. Whereas smaller telemetry probes have recently been developed, no published studies have used radiotelemetric monitoring of arterial pressure in mice, largely because of a relatively low success r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 12 publications
9
81
0
1
Order By: Relevance
“…The genetic background of our mice features DNA derived from 129/Ola strain (2 renin genes 28 ) and C57BL/6, a single renin gene strain that can also develop increased BP after salt loading. 24,29 Although the influence of salt in our genetic background may have obscured subtle changes in BP secondary to EC ET B KO, we still found that selective pharmacological antagonism of ET B during high-salt diet led to further increases in BP, as described previously in the rat. 9 Although there was no difference in BP between control and KOs during pharmacological ET B blockade, the absolute increase in BP just failed to reach statistical significance in EC-specific KOs (Pϭ0.06).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The genetic background of our mice features DNA derived from 129/Ola strain (2 renin genes 28 ) and C57BL/6, a single renin gene strain that can also develop increased BP after salt loading. 24,29 Although the influence of salt in our genetic background may have obscured subtle changes in BP secondary to EC ET B KO, we still found that selective pharmacological antagonism of ET B during high-salt diet led to further increases in BP, as described previously in the rat. 9 Although there was no difference in BP between control and KOs during pharmacological ET B blockade, the absolute increase in BP just failed to reach statistical significance in EC-specific KOs (Pϭ0.06).…”
Section: Discussionsupporting
confidence: 72%
“…Under isoflurane anesthesia, a telemetry catheter was inserted into the left carotid artery and the transmitter device (Data Sciences) secured in the left flank as described previously. 24 Mice continued standard gel chow for 7 days after surgery before commencement of high (7.6% NaClϩH 2 O ad libitum), medium (2.5% NaClϩ1% saline ad libitum), or low (0.76% NaClϩH 2 O ad libitum) salt diets. A cohort of mice at the end of the study additionally received A192621 (30 mg/kg per day) in their gel.…”
Section: Telemetry Bp Recordingmentioning
confidence: 99%
See 1 more Smart Citation
“…We elected the intra-abdominal placement of our transmitters to avoid the confounding effects of carotid catheterization in our mice. 42 The mortality of abdominal placement is higher, and the technical difficulty involved is greater. However, the amount of data we analyzed in our chronic study was substantial.…”
mentioning
confidence: 99%
“…In vivo myocardial contractile function was assessed in anesthetized mice (isoflurane) using echocardiography, as described previously (21). Ambulatory heart rate and blood pressure, as well as activity, were continuously assessed by radiotelemetry, as described previously (3). Radiotelemetric devices were surgically implanted in 11-wk-old wild-type and CCM mice, which were allowed to recover from this intervention for 1 wk before a 2-wk data collection period (i.e., 12-14 wk of age).…”
Section: Animalsmentioning
confidence: 99%